Removal of metal ions from aqueous solution by chelating polymeric hydrogel - Pereira Carvalho, Hudson Wallace [UNESP]; Batista, Ana P. L.; Hammer, Peter [UNESP]; Luz, Gustavo H. P.; Ramalho, Teodorico C. (Springer Heidelberg, 2010)
Polysaccharide natural seed coat from the tree Magonia pubescens, in the form of hydrogel was used to remove metals in aqueous solution. Swelling tests indicate that seed coat presents hydrogel behavior, with maximum water absorption of 292 g water/g. Adsorption experiments performed using Na(+), Mg(2+), K(+), Ca(2+), Cr(3+), Fe(3+) and Zn(2+) demonstrated that the polysaccharide structure has a high capacity to extract these ions from the aqueous solution. Scanning electron microscopy revealed significant morphological changes of the material before and after water contact. Differential scanning calorimetry measurements indicate a signal shift of the water evaporation temperature in the material with adsorbed zinc. X-ray photoelectron spectroscopy analysis combined with theoretical studies by the density functional theory and on Hartree-Fock (HF) level evidence that the metallic ions were adsorbed through coordination with hydroxyl groups of polysaccharide. In the case of Zn(2+) the lowest HF energy was observed for the tetracoordination mode, where Zn(2+) is coordinated by two hydroxyl groups and two water molecules.
Keywords: Hydrogel; Polysaccharide; Metallic ions; Adsorption; Hartree-Fock